PERANCANGAN KAMPANYE PSYCHOLOGICAL FIRST AID (PFA) SEBAGAI PENANGGULANGAN DISTRESS PADA REMAJA - Fidya Naya Prianka; Indira Anjani Laras; Wulan Dari Sirait (Linimasa : Jurnal Ilmu Komunikasi, 2022)
The increasing number of adolescents with mental problems, especially distress in Indonesia, is something to be worried about. However, the community's active participation in taking the time to be good listeners for distress sufferers is still low because people do not understand how to do first aid for handling distress. In fact, untreated distress can be the beginning of prolonged depression which can even be a trigger for sufferers to commit suicide. People who are expected to actively become a companion for people with distress need to know about Psychological First Aid (PFA). Therefore, through the design of the PFA campaign, the expectation is that it will be able to increase public awareness of the importance of being motivated to help sufferers of distress, especially teenagers in overcoming their problems and also reduce their problems, and even eliminate the existence of negative stigma against sufferers of distress in the society. In designing this campaign, the AISAS model is used as it allows the audience to disseminate messages from the campaign through social media. The results of this design are in the form of a campaign logo, three series of posters, a display of Instagram and Facebook content, website display, and campaign merchandise.